Mengatasi Kesenjangan Aksesibilitas dalam Pendidikan Bencana untuk Pembelajar Tunanetra Melalui Media Pembelajaran Kontekstual - Ramdan Afrian; Furqan Ishak Aksa; Zukya Rona Islami (Postgraduate, University of Mataram, 2025)
Disaster education in Indonesia often lacks inclusivity, particularly for students with visual impairments. This study investigates the learning needs and media preferences of visually impaired learners in three disaster-prone coastal regions of Aceh: East Aceh, Langsa City, and Aceh Tamiang. Using a qualitative descriptive approach, data were collected through interviews and audio-based questionnaires involving six visually impaired students, six teachers, school principals, and disaster education facilitators. Thematic analysis revealed four key findings: limited access to disaster education materials; strong preferences for audio storytelling, sound-based simulations, and tactile maps; low teacher preparedness; and weak institutional support. A visually centered curriculum, lack of training, and exclusion from drills were identified as major barriers. Most students had never participated in actual evacuation practices and relied solely on verbal explanations. These findings highlight an urgent need for multisensory, adaptive, and contextual learning tools tailored to the cognitive and sensory needs of visually impaired learners. The study contributes new insights for the development of inclusive disaster education policies and instructional strategies in high-risk areas. By addressing these barriers, disaster risk reduction efforts can become more equitable and effective for all children, regardless of disability.